Blood Pressure Stability Within Normal Range in Hypertension Patients is Closely Related to Compliance with Medication and Low Salt Diet: Kestabilan Tekanan Darah pada Penderita Hipertensi Berhubungan dengan Kepatuhan Minum Obat dan Diet Rendah Garam - Wulan D.C, Tsabita; Yardes, Nelly; Manurung, Santa; Lusiani, Dewi; Elsa Silviani, Nadhia; Endah Pangastuti, Tri; Iriana, Pramita; Sudrajat, Ace; Wartonah, Wartonah (Politeknik Kesehatan Kemenkes RI Jakarta I, 2024)
Hypertension control can be done by compliance with taking medication and a low-salt diet. Many people with hypertension are not compliant with taking medication and forget about a low-salt diet because they feel healthy. In fact, this should not happen because it will affect their blood pressure. The purpose of this study was to determine the relationship between compliance with taking medication and a low-salt diet with blood pressure stability in hypertensive patients. The research method used was quantitative analytical descriptive with a cross-sectional approach. The population in this study were all patients with hypertension who underwent outpatient treatment at the internal medicine. A total of 92 respondents were the sample of this study. Sampling was carried out using a purposive sampling technique. The results used chi square found that there was a relationship between medication adherence and blood pressure stability with a p-value of 0.001 and there was a relationship between a low-salt diet and blood pressure stability in hypertensive patients with a p-value of 0.001. The conclusion is that there is a relationship between medication adherence and a low-salt diet with blood pressure stability in hypertensive patients. Recommendations for patients with hypertension are advised to maintain salt intake and continue taking medication so that blood pressure remains stable.